PATH-52. UTILIZING NEXT GENERATION SEQUENCING REPORTS IN CLINICAL DECISION MAKING: REPORT FROM THE NATIONAL INSTITUTES OF HEALTH (NIH) NEURO-ONCOLOGY BRANCH (NOB) NATURAL HISTORY STUDY (NHS) PRIMARY BRAIN TUMOR PANEL (PBTP). (5th November 2018) - Siegel, Christine; Aboud, Orwa; Brown, Miranda; Chung, Hye-Jung; Raffeld, Mark; Crandon, Sonja; Ji, Ming; Levine, Jason; Vera, Elizabeth; Patel, Snehal; Reyes, Jennifer; Armstrong, Terri; et al.
Abstract: BACKGROUND: The use of molecular diagnostics is an integral component of CNS cancer care. The NIH NOB PBTP includes 80 alterations (55 mutations/copy number variations and 25 gene fusions) identified as relevant to the primary CNS patient population. We have previously reported on the diagnostic utility. Identified therapeutic target results from the PBTP are reported here. METHODS: PBTP results from patients enrolled on the NOB NHS are reported. Targetable alterations were defined using the NCI MATCH trial list. The proportion of cases with identified alterations based on recognized diagnostic histology and recurrence are reported. RESULTS: 190/282 (67%) PBTPs reported significant alterations; 132 from initial diagnosis and 58 recurrent samples;10 had two sequential samples analyzed. Astrocytoma, grade 2–4 (126/190, 66%), was the most common histologic tumor type. Over 60% of cases had a unique alteration profile, appearing only once in the data set. At diagnosis 74% had 1–3 alterations. At recurrence 45% had >3, and 9% had > 7 alterations. New and increasing alterations were seen in 80% (8/10) of sequential cases, with 1 case showing an entirely different alteration pattern. Targetable alterations were identified in 87/190 (46%) PBTP results. Exclusively in astrocytomas, EGFR (19%), and CDK4/CDK6 (12%) were found. Less frequent were: BRAF (5%) (8 astrocytomas, 2 pleomorphic xanthoastrocytoma), FGFR (3%) (5 GBM, 1 rosette-forming glioneuronal tumor), MET (3%) (3 GBM, 1 anaplastic oligodenroglioma, 1 anaplastic ependymoma), PTCH1 (3%) (3 astrocytoma, 1 ependymoma, 1 medulloblastoma), NTRK (2%) (2 astrocytomas, 1 oligodendroglioma). CONCLUSIONS: The PBTP has demonstrated diagnostic and therapeutic utility, with actionable targets found in nearly half of analyzed samples. The profile and number of alterations was higher at recurrence, underscoring the need for contemporary resampling and analysis. Importantly, 2/3 of the results showed a unique alteration profile highlighting the unique nature of each patients tumor.